The aetiology of upper quadrant musculoskeletal pain in high school learners using desktop computers : a prospective study - Prins, Yolandi (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScPhysio (Physiotherapy))--Stellenbosch University, 2008.